A Sensitive Luminescent Acetylacetone Probe Based on Zn‐MOF with Six‐Fold Interpenetration - Kang, Xiao‐Min; Cheng, Rui‐Rui; Xu, Hang; Wang, Wen‐Min; Zhao, Bin (Chemistry : a European journal, 2017)
A novel metal‐organic framework {[Zn(XL)2](ClO4)2⋅6 H2O}n (XL=N,N′‐bicyclo[2.2.2]oct‐7‐ene‐2,3,5,6‐tetracarboxdiimide bi(1,2,4‐triazole)) was synthesized and structurally characterized, presenting the first example of six‐fold interpenetrating 3 D framework with the topology type of sqc6, which displays high thermostability and solvent stability. Additionally, the luminescence investigations reveal that this MOF can sensitively and selectively detect acetylacetone with a detection limit of 1.72 ppm. More importantly, it is rather rare for an MOF‐based luminescence probe to serve as a sensor to effectively detect acetylacetone. Detecting acetylacetone: A novel metal–organic framework, {[Zn(XL)2](ClO4)2⋅6 H2O}n, was synthesized and structurally characterized, presenting the first example of a six‐fold interpenetrating 3 D framework with the sqc6 topology and the first example of a transition‐metal MOF‐based luminescence sensor to effectively detect acetylacetone. The detection limit achieved was 1.72 ppm.